Influence of footwear designed to boost energy return on running economy in comparison to a conventional running shoe - Sinclair, J.; Mcgrath, R.; Brook, O.; Taylor, P. J.; Dillon, S. (Journal of Sports Sciences, 2016)
Running economy is a reflection of the amount of inspired oxygen required to maintain a given velocity and is considered a determining factor for running performance. Athletic footwear has been advocated as a mechanism by which running economy can be enhanced. New commercially available footwear has been developed in order to increase energy return, although their efficacy has not been investigated. This study aimed to examine the effects of energy return footwear on running economy in relation to conventional running shoes. Twelve male runners completed 6-min steady-state runs in conventional and energy return footwear. Overall, oxygen consumption (VO2), heart rate, respiratory exchange ratio, shoe comfort and rating of perceived exertion were assessed. Moreover, participants subjectively indicated which shoe condition they preferred for running. Differences in shoe comfort and physiological parameters were examined using Wilcoxon signed-rank tests, whilst shoe preferences were tested using a chi-square analysis. The results showed that VO2 and respiratory exchange ratio were significantly lower, and shoe comfort was significantly greater, in the energy return footwear. Given the relationship between running economy and running performance, these observations indicate that the energy return footwear may be associated with enhanced running performance in comparison to conventional shoes.